Host modulatory agents in periodontics: A step towards the future - Ajay Kumar Bhatt; Vivek Govila; Mona Sharma (Wolters Kluwer Medknow Publications, 2015)
Periodontitis is a common inflammatory condition of the oral cavity. Successful management of periodontal disease and its sequelae basically focuses towards the reduction and/or elimination of pathogenic bacteria that are thought to cause periodontitis which has been accomplished by the use of mechanical treatment approaches including scaling, root planning, and finally surgical intervention. However, emerging evidence strongly suggests that it is the inflammatory response of the host that drives the tissue destruction, and the unpredictability of host responses can account for much of the variability in the clinical manifestation of periodontitis. Recently advances in study of bone metabolism are opening up new avenues of understanding regarding the bone loss subsequent to periodontitis. This knowledge, together with the development of novel drugs (e.g., alendronate, etidronate) which can inhibit bone loss/destruction, provides us with opportunities to target not only soft tissue inflammation but also the destructive bone loss occurring during periodontitis. The use of such agents as an adjunct to conventional periodontal therapy, not only reduces the current periodontal disease severity and improves treatment prognosis, but also reduce future susceptibility towards periodontal disease.